Frontiers in Hydrocephalus 2023
DOI: 10.5772/intechopen.110535
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus Associated with Myelomeningocele

Abstract: Hydrocephalus (HCP) is one of the most common associations of myelomeningocele, and it may be overt and present at birth or be latent and develop following the repair of myelomeningocele. In patients with myelomeningocele, aqueductal stenosis, fourth ventricular obstruction, subarachnoid obstruction at the tentorial hiatus, and the crowded posterior fossa, which are all related to Chiari II malformation, are the various causes of hydrocephalus. The clinical manifestations depend on the age at presentation, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Higher incidence of hydrocephalus was recorded for MM of the lower spinal region when compared segmentally, particularly lumbosacral areas in our study as shown in Figure 3. It has been reported that the rate of treated hydrocephalus in patients with myelomeningocele varies with the ana-tomic level of the lesion, 60.7% for sacral, 82.4% for lumbar, and 92.2% for thoracic [22]. We performed 7 (6.8%) ventriculo-peritoneal shunt procedures after myelomeningocele repair compared to 6 who had hydrocephalus at presentation.…”
Section: Discussionmentioning
confidence: 95%
“…Higher incidence of hydrocephalus was recorded for MM of the lower spinal region when compared segmentally, particularly lumbosacral areas in our study as shown in Figure 3. It has been reported that the rate of treated hydrocephalus in patients with myelomeningocele varies with the ana-tomic level of the lesion, 60.7% for sacral, 82.4% for lumbar, and 92.2% for thoracic [22]. We performed 7 (6.8%) ventriculo-peritoneal shunt procedures after myelomeningocele repair compared to 6 who had hydrocephalus at presentation.…”
Section: Discussionmentioning
confidence: 95%